Identidades e ancestralidades das mulheres indígenas na poética de Eliane Potiguara - Costa, Heliene Rosa da (2020)
This thesis proposes a study on the work of Brazilian indigenous writer Eliane Potiguara, especially in her work Half Face, Half Mask (2018). In it, the author presents poems, essays and articles concerning the indigenous universe, preferably on themes such as love, family, identity and human rights. The goal is to investigate how the indigenous feminine identity is built in the work. With this in mind, we verified that such identity manifests itself in different ways in the analyzed set. In first place, the inspiration for the author's literary production arose from the narratives of her indigenous grandmother, who influenced her since childhood. This correlation suggests that the constitution of indigenous feminine identity in the work is supported, through storytelling, by the the narrator's grandmother's memory and the ancestral knowledge transmitted. On the other hand, the feminine theme permeates the writer's texts, either in the defense of rights, as well as denouncing the injustices suffered by indigenous and socially excluded women. Thus, one can perceive the overlapping of poetic-literary production on behalf of the struggle for women's rights. In the sequence, one can notice an ethnic cosmovision in which the indigenous woman's gaze engenders the writing's compositional process. On the other hand, the literary expressions of the Brazilian Portuguese indigenous authors are relatively recent. On the whole, the first publications appeared a few decades ago. And, in recent years, they have increased significantly. However, it is still little known and less widespread in cultural and academic environments; and productions are often seen with resistance on the part of some readers. This authorship of the Brazilian indigenous peoples' representatives has the advantage of providing the expression from the perspective of the cultures' interior from the many indigenous peoples that compose the Brazilian social fabric. This study is based on theorists Stuart Hall, Eurídice Figueiredo, Margareth Rago, Gayatri Chakravorty Spivak, Gaston Bachelard, Luiza Lobo, Alfredo Bosi, Liane Schneider and works by indigenous writers: Eliane Potiguara, Graça Graúna, Ailton Krenak, Daniel Munduruku, Márcia Wayna Kambeba, Lia Minapoty, Auritha Tabajara; Kaká Werá, Sônia Bone Guajajara; Yaguarê Yamã, among others. The indigenous literature acts in favor of the various indigenous communities' safeguard of memory, identity and ancestry. Thus, the production and diffusion of Eliane Potiguara's work's systematized knowledge can contribute to minimize issues related to prejudice against indigenous peoples. We believe that Literature, through its multiple manifestations and specificities, mainly for its artistic potential of representing our humankind, may.